Facio-Scapulo-Humeral Muscular Dystrophy - A Case Report - Dey, Arjun Chandra; Mannan, Mohammad Abdul; Chowdhury, Forhad Hossain; Mostofa, Gazi Golam; Saha, Laxmi (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v33i3.5693 Bangladesh Journal of Child Health 2009; Vol.33(3): 114-116